Design and Experiment of a Teaching Tool for Oval Gears with Variable Transmission Ratio. Issue 2 (March 2021) - Huang, Zhidong; Zhi, Shan; Shi, Chunyang
Abstract: The basic theory of oval gear is studied. The teaching tool with variable transmission ratio of oval gear is designed. On the premise that the center distance remains unchanged, the parameter law of oval gear is clarified, and finally oval gear mechanism parameters of meeting the constraint conditions of box body are obtained. The effectiveness of the teaching tool design method is verified by experiments, which facilitates the standardized design and application of oval gear.